Staying close: short local dispersal distances on a managed forest of two Patagonian Nothofagus species - Sola, Georgina Giselle (2020)
Understanding the impact of management on the dispersal potential of forest tree species is pivotal in the context of global change, given the implications of gene flow on species evolution. We aimed to determine the effect of logging on gene flow distances in two Nothofagus species from temperate Patagonian forests having high ecological relevance and wood quality. Therefore, a total of 778 individuals (mature trees and saplings) of Nothofagus alpina and N. obliqua, from a single plot managed 20 years ago (2.85 hectares), were mapped and genotyped at polymorphic nuclear microsatellite loci. Historical estimates of gene dispersal distance (based on fine-scale spatial genetic structure) and contemporary estimates of seed and pollen dispersal (based on spatially explicit mating models) were obtained. The results indicated restricted gene flow (gene distance ≤ 45 m, both pollen and seed), no selfing and significant seed and pollen immigration from trees located outside the studied plot but in the close surrounding area. The size of trees (diameter at breast height and height) was significantly associated with female and/or male fertility. The significant fine-scale spatial genetic structure was consistent with the restricted seed and pollen dispersal. Moreover, both estimates of gene dispersal (historical and contemporary) gave congruent results. This suggests that the recent history of logging within the study area has not significantly influenced on patterns of gene flow, which can be explained by the silviculture applied to the stand. The residual tree density maintained species composition, and the homogeneous spatial distribution of trees allowed the maintenance of gene dispersal. The short dispersal distance estimated for these two species has several implications both for understanding the evolution of the species and for defining management, conservation and restoration actions. Future replication of this study in other Nothofagus Patagonian forests would be helpful to validate our conclusions.